2017
DOI: 10.1002/jum.14368
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Pattern Analysis on Microvascular Sonography for Differentiation of Pleomorphic Adenomas and Warthin Tumors of Salivary Glands

Abstract: Vascular pattern analysis using microvascular sonography with other sonographic features is helpful for differentiating between pleomorphic adenomas and Warthin tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A few studies have reported that SMI could be useful for improving the diagnostic performance during the assessment of cervical LNs [ 21 , 22 , 23 ] and salivary gland tumors [ 24 ]. However, its clinical utility for the prediction of PTC metastasis in LNs has not yet been validated.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported that SMI could be useful for improving the diagnostic performance during the assessment of cervical LNs [ 21 , 22 , 23 ] and salivary gland tumors [ 24 ]. However, its clinical utility for the prediction of PTC metastasis in LNs has not yet been validated.…”
Section: Introductionmentioning
confidence: 99%
“…However, our study group included only 4 malignant lesions, and so the statistical comparison Evaluation of benign parotid gland tumors with superb microvascular imaging and shear wave elastography parotid gland, but we only measured the vascular index of the tumor via drawing the lesion borders. A very recent study conducted by Ryoo et al (13) in 2018 investigated SMI in pleomorphic adenoma and Warthin tumors of the salivary glands. The authors of that study graded the internal vascularity of salivary gland tumors using a 5-point scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few reports can be found in the literature which evaluate the role of SMI in parotid gland tumors. Previous studies with SMI have addressed thyroid gland, lymph nodes, testes, and breast lesions (10,13,(25)(26)(27)(28)(29) .…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are few clinical studies on ultra-micro angiography of parotid gland tumors [ 12 ]. In this study, we compared the diagnostic performance of SMI and CDFI, and analysis correlation between SMI, CDFI and MVD, so as to explore the clinic value for SMI assess micro vascular density.…”
Section: Introductionmentioning
confidence: 99%